Institutional Structure and Labor Market Outcomes : Western Lessons for European Countries in Transition - Flanagan, Robert (Washington, D.C. : International Monetary Fund, 1995)
Changes in economic systems provide a rare opportunity to redesign basic institutional structures in labor markets. This paper attempts to provide guidance for such institutional choice by drawing on the findings of recent labor market research in market economies on the links between institutional structure and labor market performance. After considering the suitability of research from market economies for the labor market problems faced by economies in transition from central planning, the paper considers the effects of alternative institutions for wage determination (collective bargaining structures and minimum wage and indexation legislation), employment security, income security, and active labor market policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet